2019
DOI: 10.1002/ece3.5631
|View full text |Cite
|
Sign up to set email alerts
|

Seagrass‐associated fungal communities show distance decay of similarity that has implications for seagrass management and restoration

Abstract: Marine fungal biodiversity remains vastly understudied, and even less is known of their biogeography and the processes responsible for driving these distributions in marine environments. We investigated the fungal communities associated with the seagrass Enhalus acoroides collected from Singapore and Peninsular Malaysia to test the hypothesis that fungal communities are homogeneous throughout the study area. Seagrass samples were separated into different structures (leaves, roots, and rhizomes), and a sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 73 publications
12
27
0
Order By: Relevance
“…Like other studies examining microbial diversity and coral-associated bacteria throughout Singapore and the region, we show significant differences in microbial community structure among sampling locations 10,24,39,40 . All samples are generally dominated by Proteobacteria and Cyanobacteria, and samples collected from Tanah Merah appear most distinct in comparison to other sites.…”
Section: Discussionsupporting
confidence: 71%
“…Like other studies examining microbial diversity and coral-associated bacteria throughout Singapore and the region, we show significant differences in microbial community structure among sampling locations 10,24,39,40 . All samples are generally dominated by Proteobacteria and Cyanobacteria, and samples collected from Tanah Merah appear most distinct in comparison to other sites.…”
Section: Discussionsupporting
confidence: 71%
“…In addition to differences in alpha diversity, we also observed differences in fungal community structure across tissues and sites. Differences in fungal beta diversity across sites and tissues has been reported previously for seagrasses (Bengtsson et al, 2017;Wainwright et al, 2018Wainwright et al, , 2019bHurtado-McCormick et al, 2019;Ettinger & Eisen, 2019;Trevathan-Tackett et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
“…Previous work on the fungal community associated with the seagrass, Enhalus acoroides, identified a pattern of distance decay, where the fungal community was more similar between seagrass that were closer together geographically than between seagrass that were distant from each other [46]. This suggests that dispersal limitation and/or habitat specialization are playing important roles in structuring the fungal community associated with seagrasses.…”
Section: Plos Onementioning
confidence: 96%
“…Culture-based studies have found fungi associated with leaves, roots and rhizomes of seagrasses, but there is little agreement between studies about the taxonomic composition of these communities within and between seagrass species [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Recently cultureindependent studies of seagrass-associated fungi have more thoroughly investigated the diversity of these microorganisms and highlighted a need to further understand factors affecting their biogeography and community dynamics [43][44][45][46]. However, these studies were severely hampered by a lack of representation of fungal sequences from the marine environment in public databases and found that taxonomic assignments could not be made for many fungal sequences associated with seagrasses.…”
Section: Introductionmentioning
confidence: 99%